INFECTIVE ENDOCARDITIS AND ANTIBIOTIC PROPHYLAXIS – AN UPDATE FOR DENTAL PRACTITIONERS - DR. M.P.SANTHOSH KUMAR (International Journal of Pharma and Bio Sciences, 2015)
Infective endocarditis [IE] is an uncommon but life-threatening complication resulting from bacteremia, bacteria in the blood stream. Dental procedures can induce bacteremia, so it is essential to give prophylactic antibiotics for patients with cardiac disease who are at risk of developing infective endocarditis. In this article the current recommendations for dentists regarding antibiotic prophylaxis against infective endocarditis as per American heart association 2007 revised guidelines is presented. In addition to summary of the indications for prophylaxis, information is provided on the conditions for which prophylaxis is not recommended.